Pengaruh Sandwich Laminated Coco Mat Dan Chopped Strand Mat Terhadap Kekuatan Material Komposit - Tarkono, Tarkono (Semesta Teknika, 2016)
The application of coco fibre is widely open. In rural area, as a main source of coco fibre, the fibre only used for cooking and family products. As the technology development, how coco fibre can applied as a part of composites materials. If it compound with other specific components, we can produce a new material with better mechanical properties. In this research, coco fibre with 0,2% wetness, compound with latex then pressed to get a coco mat with 2 mm thickness. Coco mat then formed with chopped strand mat to get a sandwich laminate composite. The original tensile strength of coco mat is 2,47 kgf/mm2 will increased to 12,93 kgf/mm2 if it formed as sandwich laminate coco fibre, its tensile strength improve about 80,90%.